PENYEBAB OBAT KEDALUARSA, OBAT RUSAK DAN DEAD STOCK (STOK MATI) DI GUDANG PERBEKALAN FARMASI GUDANG PERBEKALAN FARMASI RUMAH SAKIT X SURABAYA - Nurcahyani, Diah; Ayuningtyas, Arina; G, Leo Eladisa (Jurnal Riset Kefarmasian Indonesia, 2023)
Drug processing problems in each hospital often occur nowadays, so it is necessary to carry out continuous evaluation to create optimal services in providing good quality patient health. This study aims to describe and analyze the occurrence of expired drugs, damaged drugs and dead stock, to provide policy recommendations for improving drug processing. This study uses a descriptive method, namely research that describes an object in relation to the actual situation. The sample used in this study is the number of expired drugs, damaged drugs and dead stock for the period June - August 2021 compared to the total number of drugs in the hospital. The percentage results for expired drugs were 0.002%, damaged drugs were 0%, dead stock were 0.022%, this was due to changes in prescribing patterns, expiration dates that were too short when receiving drugs from PBF and not maximally checking expired drugs in each unit, so it is necessary to do checking between planning and drug needs as well as improving the ED drug processing system and evaluating the system and evaluating the drug acceptance system in hospitals.